Understanding of the Readiness for HTA Implementation in Jordan as a Step Towards Universal Health Coverage - Alamer, Mira; Kaló, Zoltán; Schuller, Tara; Almomani, Emad; AlQutob, Raeda (Jordan Medical Journal, 2023)
As Jordan strives to achieve universal health coverage, the mechanism for determining which health technologies to include in the basket of reimbursed services has become increasingly important. This study sought to understand stakeholder perspectives in the Jordanian health system regarding the readiness and need to implement health technology assessment (HTA) to support decision-making quality and transparency, ensure value for money on health system spending, and support the achievement of universal health coverage. This study used a cross-sectional survey methodology, and a quantitative analysis was conducted. A questionnaire based on the HTA implementation scorecard was administered in-person to capture responses regarding fourteen dimensions. Thirty-one responses from representatives across the Ministry of Health, regulatory authority, and other stakeholders in the national health system were collected. Most respondents were familiar with HTA and there was nearly unanimous agreement on the need for HTA implementation in Jordan. While the perspectives on how the implementation would occur were varied, careful consideration may be warranted in the areas of the legal framework for HTA, the quality of available data, financial constraints, and limited human resource capacity, as Jordan progresses towards implementing HTA on the road to universal healthcare.